P070 Global cytokine—cytokine interaction framework to uncover communication channels between elements of the immune system. (30th January 2023) - Olbei, M; Modos, D; Cozzetto, D; Powell, N; Korcsmaros, T
Abstract: Background: Cytokines are small peptides that signal between a variety of cell types and are one of the fundamental communication elements of the immune system. A variety of cytokine—cytokine interactions have previously been investigated in the literature, describing cytokines activating or inhibiting other cytokines in target cell types, and thus progressing the immune response to infection and illness. Disruption of cytokine communication is often an important goal in drug development as these compounds allow quelling and managing an overactive immune response in chronic diseases, such as Inflammatory Bowel Disease (IBD). In our previous work, we have introduced CytokineLink, a novel computational framework developed to establish cytokine—cytokine interactions from transcriptomics data (Olbei et al., Cells, 2021). Methods: In this project, we generated a global network of cytokine—cytokine interactions based on cytokine response transcriptomics data from over 2000 datasets deposited in the CytoSig database. Using CytoSig's significance analysis protocol, we established statistically significant cytokine—cytokine interactions, and determined the likely intracellular pathways connecting upstream and target cytokines using the OmniPath interaction resource. Results: The resulting network is a signed, directed network of cytokine communication, containing 488 cytokine—cytokine interactions of 91 cytokines. The interactions in the network are annotated with the intracellular pathways that the included cytokines are anticipated to utilise, as well as the stimulatory and inhibitory effects that the cytokines have on one another. The resource captures the cytokine—cytokine networks of cytokines crucial in the pathophysiology of IBD, such as TNF, IL2, IL21, and OSM, which may grant novel insights into the cytokine pathways important in the molecular mechanisms underlying chronic diseases like IBD. The resource can be used by the community as a knowledge base for hypothesis generation, and is freely available through the NDEx platform. Conclusion: In our work, we generated a novel computational framework collating how cytokines differentially regulate the expression of one another based on cytokine response transcriptomics data. The resulting interactions are signed, highlighting the inhibitory or stimulatory nature of the associations, and the change in expression associated with each link. The resource could be used to identify previously unknown network pharmacology targets, and to better understand the cytokine dysregulation in chronic diseases such as IBD by illustrating the interplay of the most influential IBD associated cytokines with other cytokines.